2007
DOI: 10.1111/j.1365-313x.2007.03244.x
|View full text |Cite
|
Sign up to set email alerts
|

Global gene expression analysis of the shoot apical meristem of maize (Zea mays L.)

Abstract: SummaryAll above-ground plant organs are derived from shoot apical meristems (SAMs). Global analyses of gene expression were conducted on maize (Zea mays L.) SAMs to identify genes preferentially expressed in the SAM. The SAMs were collected from 14-day-old B73 seedlings via laser capture microdissection (LCM). The RNA samples extracted from LCM-collected SAMs and from seedlings were hybridized to microarrays spotted with 37 660 maize cDNAs. Approximately 30% (10 816) of these cDNAs were prepared as part of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
103
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(109 citation statements)
references
References 74 publications
6
103
0
Order By: Relevance
“…2F), indicating the presence of substantially active TEs or TE fragments in maize seed development. Although it remains to be determined whether these NTRs have any biological function, some evidence has shown that TE-related regions are widely active and have acquired specific cell functions during their evolution (Vicient et al, 2001;de Araujo et al, 2005;Ohtsu et al, 2007;Lopes et al, 2008;Picault et al, 2009), and we did observe 46 TE-associated NTRs with EST evidence in addition to the support of our RNA-seq data (Fig. 2F).…”
Section: Discovery Of Ntrssupporting
confidence: 74%
“…2F), indicating the presence of substantially active TEs or TE fragments in maize seed development. Although it remains to be determined whether these NTRs have any biological function, some evidence has shown that TE-related regions are widely active and have acquired specific cell functions during their evolution (Vicient et al, 2001;de Araujo et al, 2005;Ohtsu et al, 2007;Lopes et al, 2008;Picault et al, 2009), and we did observe 46 TE-associated NTRs with EST evidence in addition to the support of our RNA-seq data (Fig. 2F).…”
Section: Discovery Of Ntrssupporting
confidence: 74%
“…Several improvements were made in tissue fixation and handling (Supplemental Fig. S7), including the adoption of acetone fixation (Ohtsu et al, 2007), the minimization of section ribbon expansion time (in water) on slides, and the use of only freshly dewaxed slides for laser capture.…”
Section: Optimization Of the Lcm Procedures And The Data Analysesmentioning
confidence: 99%
“…S1B). Before LCM, tissues were fixed in ice-cold 100% (v/v) acetone (Ohtsu et al, 2007), exchanged for acetone:Hemo-De (50:50; Scientific Safety Solvents), and then exchanged for 100% (v/v) Hemo-De. Fixation vials were placed at 60°C, and paraplast Plus chips (Leica Microsystems) were added gradually to the Hemo-De to slowly infiltrate the tissue with wax.…”
Section: Floral Tissue Isolationmentioning
confidence: 99%
“…Similar to the SAM, lateral shoot meristems undergo vegetative growth, first initiating a bikeeled prophyll followed by foliar husk leaves before transitioning into an inflorescence meristem or undergoing senescence ( Figures 1F and 1L) (Kiesselbach, 1949). Previous studies have analyzed transcripts encoded in various hand-dissected and laser-microdissected shoot apices from 14-d-old seedlings using microarray analysis, as well as 454-based and Illumina-based RNA sequencing (RNA-seq) (Emrich et al, 2007;Ohtsu et al, 2007;Brooks et al, 2009;Jia et al, 2009;Nogueira et al, 2009). However, as yet, no transcriptomic analyses of maize SAM ontogeny during embryogenesis have been described.…”
Section: Introductionmentioning
confidence: 99%